The future of accreditation of continuing medical education (CME)-continuing professional development (CPD) in Europe: harmonisation through dialogue and consensus. Issue 1 (1st January 2018) - de Andrade, Fabiola; Griebenow, Reinhard; Costello, Richard W.; Guenova, Margarita; Schaefer, Robert; Chalmers, James D.; Tichelli, Andre; Raguz, Drazen; Stein, Joerg
ABSTRACT: In Europe, there are currently some 30 different jurisdictions and no overarching legislation regarding CME-CPD accreditation, since legislative competency related to national health-care systems lies with national authorities. Thus, public demonstration of professional agreement regarding the principles, rules and practice of CME-CPD as well as its accreditation is a highly desirable professional and political objective in Europe, where free movement and freedom to offer professional (medical) services is a key feature of the EU vision of the single market. The newly formed association of independent European accreditors, Continuing Medical Education - European Accreditors (CME-EA) is committed to offering a platform for dialogue between individuals and organisations involved in definition of professional codes in general, and accreditation of CME-CPD in particular on the national level. The aim is to reach a European consensus on principles and rules applied in planning and delivery of CME-CPD. This includes consensus on constituent characteristics of accreditors as well as principles and practice of accreditation.